Market Penetration Strategy by Increasing Firm Competitiveness - Harahap, Minta Ade Doliana; Soemitra, Andri; Rahma, Tri Inda Fadhila (Golden Ratio of Marketing and Applied Psychology of Business, 2025)
To achieve successful market penetration, businesses must navigate complexities related to culture, legal frameworks, economic conditions, and competition. Businesses must decide whether to standardize their marketing strategies across different markets or adapt them to suit unique market characteristics. Competition is the ability to perform better, and faster. In facing competition, companies need to determine the right strategy, because in general companies are trying to survive, grow and develop. The purpose of the Market Penetration Strategy research by Increasing Company Competitiveness can include several aspects, namely, Assessing the company's strengths and weaknesses. Conducting market analysis to understand existing opportunities and challenges, including consumer preferences and behavior, and market trends and Developping an effective Market Penetration Strategy to increase market penetration, such as products, improving customer service, or competitive pricing strategies. This study uses a descriptive qualitative method to find out how PT. AJS Bumiputera markets its products, using market penetration to increase competitiveness, or to find out what the biggest challenges are in its market penetration strategy. This study uses a qualitative method as one of the methodologies in research that does not yet have a standard definition and is generally agreed upon for use. From the results of the study it is known that PT. Bumiputera Sharia Life Insurance, using market penetration through digital platforms such as social media, company websites, and online advertising campaigns to reach a wider audience. Organizing events, seminars, or workshops, related to finance or health. Providing education about the benefits of insurance products to the public, conducting direct promotions through telemarketing, or face-to-face marketing to introduce products directly.